OPEN CAP SPLINT WITH CIRCUMMANDIBULAR WIRING IN MANAGEMENT OF PEDIATRIC MANDIBULAR PARASYMPHYSIS FRACTURE:A DEFINITIVE CONSERVATIVE TREATMENT MODALITY - Dr. Sujeet Pal, Dr. Debangana Choudhury, Dr. Abhimanyu Singh, Dr. Manish Kumar, Dr. Preeti Sharma, Dr. Shivansh Shekhar, Dr. Debangana Choudhury (Chelonian Research Foundation, 2023)
The most frequent facio-skeletal traumatic injuries seen in children are fractures of the mandibular parasymphysis and symphysis. The complexity of the developing mandible's anatomies, as well as its patients' psychological and physiological qualities, make it difficult for paediatric dentists to manage these injuries. Mandibular parasymphysis/symphysis fractures in children can be treated using a variety of techniques, each of which has drawbacks and problems. In the current case report, an open cap splint-treated paediatric mandibular parasymphyseal fracture is described as having been successfully managed conservatively.